Coronary Risk Factors and Collateral Circulation in Acute Myocardial Infarction - Sumargo, Sheila; Dewanto, Julius B.; Hidayat, Syarief (Althea Medical Journal, 2015)
Background: Coronary arterial stenosis, the major cause of acute myocardial infarction (AMI), inducesÂ shear stress to surrounding arteriolar endothelium. This stimulates changes in endothelial cells, smoothÂ muscle cells and fibroblast to create collaterals that can provide alternative blood flow to the jeopardizedÂ myocardial area. However, coronary collateralization is various among AMI patients. The aim of this studyÂ was to analyze the correlation between coronary risk factors and collateral sirculation in AMI patients.Methods: A retrospective cross-sectional study was carried out to 148 medical records of hospitalized AMIÂ patients in Dr. Hasan Sadikin General Hospital Bandung, Indonesia. All patients were assessed for coronaryÂ collateral circulation which were graded as good (Rentrop score 2â3) and poor (Rentrop score 0â1). RiskÂ factors noted in this study were age group, sex, hypertension, diabetes mellitus and diagnosis (ST-segmentÂ Elevation Myocardial Infarction (STEMI) or Non STEMI (NSTEMI)) according to the medical record data.Â Results: Hypertension was found to be associated with the presence of good coronary collateral circulationÂ (p=0.02, PR=1.410 [95% CI 1.030-1.930]). Sex, age group, diabetes mellitus and STEMI or NSTEMI diagnosisÂ were not statistically significant.Conclusions: Hypertension was the only coronary risk factor associated to the presence of well-developedÂ coronary collaterals. The increase of myocardial oxygen demand and flow of collateral feeding coronaryÂ artery in the setting of hypertension may contribute to the results.Â Â DOI:Â 10.15850/amj.v2n4.688